2000
DOI: 10.1002/(sici)1097-0282(200005)53:6<484::aid-bip5>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ΔEPhe-containing tripeptide via photoisomerization and its conformation in solution

Abstract: A new synthetic route to (E)‐β‐phenyl‐α,β‐dehydroalanine (ΔEPhe)‐containing peptide was presented via photochemical isomerization of the corresponding (Z)‐β‐phenyl‐α,β‐dehydroalanine (ΔZPhe)‐containing peptide. By applying this method to Boc–Ala–ΔZPhe–Val–OMe (Z‐I: Boc, t‐butoxycarbonyl; OMe, methoxy), Boc–Ala–ΔEPhe–Val–OMe (E‐I) was obtained. The identification of peptide E‐I was evidenced by 1H‐nmr, 13C‐nmr, and uv absorption spectroscopy, elemental analysis, and hydrogenation. The conformation of peptide E‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The product was purified by recrystallization from ethyl acetate/n-hexane. Peptide 2 showed no minor peaks, 25 suggesting its diastereomer in the 1 H NMR spectra, but marked CD signals ([] 310 ϭ 4.0 ϫ 10 4 in CHCl 3 ), indicating that the combination of saponification and fragment condensation processes leads to no racemization essentially. Yield 1.29 g (81 %); mp 126 -130°C; …”
Section: Synthesis Of Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…The product was purified by recrystallization from ethyl acetate/n-hexane. Peptide 2 showed no minor peaks, 25 suggesting its diastereomer in the 1 H NMR spectra, but marked CD signals ([] 310 ϭ 4.0 ϫ 10 4 in CHCl 3 ), indicating that the combination of saponification and fragment condensation processes leads to no racemization essentially. Yield 1.29 g (81 %); mp 126 -130°C; …”
Section: Synthesis Of Peptidementioning
confidence: 99%
“…The program PEPCON, written by M. Sisido (private communication) for a conformational energy calculation 29 and graphics 32 of a given peptide, was modified to be applicable to ␤-aryldehyroalanine-containing peptides. [23][24][25][33][34][35][36] …”
Section: Conformational Energy Calculationmentioning
confidence: 99%
“…These progression curves were analyzed by applying standard kinetic equations, 21 which unequivocally indicated that the studied reaction is of the first order, with k1 value of (12.43 ± 0.27)×10 Preparative conversion of substituted Z ΔPhe into E ΔPhe, 22 as well as such isomerization of this dehydroamino acid in several peptides has been described previously. 23,24 However, these papers, dedicated to the photochemical reactions of slightly different aromatic dehydroamino acids, state that this process is not so simple and is accompanied by variable photochemical cyclizations. 25,26 Our study, however, does not indicate the presence of any other products than Gly-E ΔPhe in the case of this photochemical reaction, and no cyclization products were found even after long irradiation of reaction mixture, irrespective of which analytical method was used.…”
Section: Resultsmentioning
confidence: 88%
“…14 The program PEP-CON 30,31 for a conformational energy calculation and graphics of a given peptide was modified to be applicable to ␤-aryldehyroalanine-containing peptides. [32][33][34][35] The stepwise elongation 36,37 of the repeating unit -(Ala-⌬ Z Nap-Leu)-was used to find the stable conformations from all possible candidates. In the first step, energy minimization of the tripeptide, Ac-Ala-⌬ Z Nap-Leu-OMe (Ac ϭ acetyl), was carried out.…”
Section: Conformational Energy Calculationsmentioning
confidence: 99%